From Familiar Patterns, Love Finds Its Form: Family Functioning and Romantic Competence in Emerging Adulthood - Abelia Lintang Sari; Chamilul Hikam Al Karim (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Emerging adulthood is a crucial period in the development of romantic relationships, characterized by exploration in building more intimate and meaningful connections. However, not all individuals engage in romantic relationships adaptively, as evidenced by the increasing prevalence of toxic relationships. This indicates that romantic involvement does not always reflect the ability to establish healthy relationship. Romantic competence becomes essential as it encompasses the skills to understand, manage, and maintain romantic relationships in an adaptive way. Family functioning serves as a key factor in the development of romantic competence, as it is the first environment where individuals learn interaction patterns and interpersonal relations. This study aims to examine the relationship between family functioning and romantic competence among emerging adults. This study uses a correlational quantitative approach with a cross-sectional design. The participants consisted of 198 emerging adults aged 18–25 years, selected through purposive sampling techniques. Data were collected using the Family Assessment Device (FAD) to measure family functioning and the Inventory of Romantic Relationship Competence (IRRC) to measure romantic competence. Data analysis was conducted using Spearman's correlation test with IBM SPSS 27. The results revealed a positive and significant relationship between family functioning and romantic competence (r = 0.417, p < 0.001). This finding interprets that higher levels of family functioning are associated with a greater ability to engage in adaptive romantic relationships. Overall, the findings suggest that the quality of family relationships serves as a “blueprint” for the interaction patterns individuals develop in their romantic relationships during early adulthood.Emerging adulthood merupakan periode krusial dalam perkembangan relasi romantis, ditandai oleh eksplorasi dalam membangun hubungan yang lebih intim dan bermakna. Faktanya, tidak semua individu mampu menjalani hubungan romantis secara adaptif, terbukti dari semakin maraknya fenomena toxic relationship. Situasi tersebut menunjukkan bahwa keterlibatan dalam hubungan romantis tidak selalu disertai dengan kemampuan untuk menciptakan relasi yang sehat. Romantic competence menjadi esensial untuk dimiliki individu karena mencakup keterampilan dalam memahami, mengelola, dan mempertahankan hubungan romantis secara adaptif. Family functioning menjadi faktor yang berperan penting dalam pembentukan romantic competence. Keluarga menjadi lingkungan pertama bagi individu dalam mempelajari pola interaksi dan relasi interpersonal. Penelitian ini bertujuan untuk mengetahui hubungan antara family functioning dan romantic competence pada individu emerging adulthood. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan desain cross-sectional. Partisipan berjumlah 198 individu emerging adulthood berusia 18–25 tahun, yang dipilih melalui teknik purposive sampling. Pengumpulan data menggunakan instrumen Family Assessment Device (FAD) untuk mengukur family functioning dan Inventory of Romantic Relationship Competence (IRRC) untuk mengukur romantic competence. Analisis data dilakukan menggunakan uji korelasi Spearman dengan bantuan IBM SPSS 27. Hasil penelitian menunjukkan hubungan positif dan signifikan antara family functioning dan romantic competence (r = .417, p < .001), yang menginterpretasikan bahwa semakin tinggi tingkat keberfungsian keluarga, semakin tinggi pula kemampuan individu dalam menjalin hubungan romantis secara adaptif. Temuan ini mengindikasikan bahwa kualitas relasi dalam keluarga berperan sebagai “blueprint” bagi pola interaksi yang dikembangkan individu dalam hubungan romantis pada masa dewasa awal.